PENGARUH TERPAAN INFORMASI PERTAMBAHAN JUMLAH KORBAN COVID-19 DI KOMPAS TV TERHADAP KECEMASAN MASYARAKAT (Survei Pada Generasi Milenial Kelurahan Pesanggrahan) - Sania Chandra Nurfitriana (2021)
2019 is the beginning of the year for the emergence of a virus which is currently a global public health emergency pandemic. News in both electronic and non-electronic media has become busy reporting the number of Covid-19 victims per day, one of them is Kompas TV. This study will explain the relationship between the effect of exposure information on the increase the number of Covid-19 victims on Kompas TV to public anxiety, especially in the millennial generation. This study uses Cultivation Theory, which explained that if television media hit the audience often it will affect to their perceptions and behaviour. The research method uses quantitative with the survey method, by distributing questionnaires to 100 respondents of Pesanggrahan Urban Village Community aged 21 to 36. The results of this study showed that there was 13,1% the effect of exposure information on the increase of the number Covid-19 victims on Kompas TV to public anxiety. The hypothesis also shows that Ho is rejected and H1 accepted. So the conclusion of this study is there is an effect of exposure information on the increase of the number Covid-19 victims to the anxiety of Millenial Community of Pesanggrahan Urban Village.